Dinamika demokrasi pros prosedural vs demokrasi substantif di indonesia pasca pemilu 2024: tantangan representasi dan partisipasi publik - Maulidya, Aprilla (Maliki Interdisciplinary Journal, 2026)
Democracy is a system of government that places the people as the ultimate holders of sovereignty in the life of the nation. The development of democracy in Indonesia has undergone significant changes since the Reformation era, particularly in the political, legal, and constitutional spheres. Democracy is not only about the conduct of general elections, but also encompasses public participation, law enforcement, the protection of human rights, and oversight of the government’s operations. However, the practice of democracy in Indonesia still faces various challenges, such as political populism, low public participation, the spread of misinformation, and weak law enforcement. This study aims to explain the importance of public participation, substantive democracy, and the role of state institutions in maintaining democratic stability in Indonesia. The findings indicate that a well-functioning democracy is not merely focused on formal procedures like elections but must also foster social justice, public welfare, and the protection of citizens’ rights. Furthermore, strengthening the legal system, constitutional reform, and the existence of independent state institutions are crucial factors in fostering a transparent and accountable government. Therefore, collaboration between the government and the public is essential to enhance the quality of democracy in Indonesia.